SPEECH ACTS OF RELIGIOUS MODERATION IN VAKIL AND VAKIL'S DIGITAL COMIC '40 SUFI' - Aris Hidayatulloh; Abdul Ayiz; Hilal Rahmadan; Lukman Abdul Mukti (UIN Raden Mas Said Surakarta, 2024)
This study discusses representative speech acts in digital comic discourse created by Mohammed Arif Vakil and Mohammed Ali Vakil reflecting the religious moderation among societies. The comic discourse campaigns for the importance of tolerance between human beings. The analysis focuses on the reflection of religious moderation in one chapter entitled ‘Ethic’ which describes the relation among human beings. The chapter is chosen due to its message which focuses on relation among people. The data of this research were obtained from the whole texts and pictures in the chapter. The texts in the comic became the main data whereas the images were put as secondary data. These data were then processed and classified into several speech act classifications proposed by Searle. The result shows that the most dominant speech act performed by the comic maker is representative speech acts. Meanwhile the directive speech acts are commonly used to give the direct moral lessons. The chapter reflects religious moderation in three points i.e. (1) applying good attitudes to others; (2) reflecting the moral value; (3) helping others without hurting the feelings by applying the representative and directive speech acts to convey the religious moderation. The representative speech acts function as the utterances of giving statement and admitting about something related with good deeds and never hurting others while the directive speech acts functions as the utterances of requesting, asking, and recommending certain things. The directive speech acts take the roles as the directive meanings on moral values.